Persepsi Siswa Terhadap Proses Penerapan Pembelajaran Pendidikan Jasmani Olahraga Dan Kesehatan Pada Pandemi Covid-19 - Apta Melyza; Rachmi Marsheilla Aguss (Universitas Teknokrat Indonesia, 2021)
AbstractThis study aims to find out about students' perceptions of the process of implementing sports and health physical education learning in the covid-19 pandemic at SMA Negeri 1 Padang Cermin. This research is a quantitative descriptive. The method used is a survey with data collection techniques using a questionnaire. The population in this study was 588 students consisting of class X and XI at SMA Negeri 1 Padang Cermin and the sample of this study was 88 students in class X and XI. The data analysis technique used was quantitative descriptive analysis as outlined in the percentage. The results of the research on student perceptions of the process of implementing sports and health physical education learning in the covid-19 pandemic at SMA Negeri 1 Padang Cermin, it can be concluded that they are in the